Myokines: Novel therapeutic targets for diabetic nephropathy - Yang, Ming; Luo, Shilu; Yang, Jinfei; Chen, Wei; He, Liyu; Liu, Di; Zhao, Li; Wang, Xi (Frontiers in Endocrinology, 2022)
With the increasing incidence of diabetic nephropathy (DN), there is an urgent need to find effective DN preventive and therapeutic modalities. It is widely believed that effective exercise is good for health. However, the beneficial role of exercise in kidney disease, especially in DN, and the underlying molecular mechanisms have rarely been reported. Muscle is not only an important motor organ but also an important endocrine organ, secreting a group of proteins called “myokines” into the blood circulation. Circulating myokines then move to various target organs to play different biological roles. In this review, we summarize the currently known myokines and the progress in research relating them to DN and discuss its potential as a therapeutic target for DN.